PERAN KOMISI PENYIARAN INDONESIA DAERAH RIAU (KPIDR) DALAM MEMBERIKAN AKSESIBILITAS INFORMASI PUBLIK SEBAGAI BENTUK PEMENUHAN HAK BAGI DISABILITAS RUNGU BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2002 TENTANG PENYIARAN DI PROVINSI RIAU - Idris Frenagen; Emilda Firdaus; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Public service is a government responsibility. Information and communication is of course one of the important things in the public service system. This is guaranteed in article 28F of the 1945 Constitution and various other regulations, such as Law Number 39 of 1999 concerning Human Rights and Law Number 32 of 2002 concerning Broadcasting. The delivery of information and communication by television in the Riau Province has not fully guaranteed the right to accessibility for Deaf Disabilities. Regional Regulation of Riau Province Number 18 of 2013 concerning Protection and Empowerment of Persons with Disabilities guarantees the right to facilitate obtaining information for Deaf people.This type of research is sociological. This research was conducted at the Riau Regional Indonesian Broadcasting Commission, Riau Province Social Service, Riau's Tuli Lancang Kuning Community and Commission I for Information/press, the Regional Representative Council of Riau Province, while the sample population was all parties related to the problem under study. Sources of data used are primary and secondary data, data collection techniques are observation, questionnaires, interviews and literature review.In the research results, there are three main points that can be concluded. First, the implementation of Law Number 32 of 2002 concerning Broadcasting in ensuring the provision of accessibility of public information for deaf people in Riau Province has not been carried out properly. Second, the Inhibiting Factors of the Riau Regional Indonesian Broadcasting Commission in guaranteeing public services for the right to information accessibility for deaf people in Riau Province are Weaknesses of Regulation, Lack of Active Participation of Affected Communities and Lack of Budget for Broadcasting Institutions in Providing Information Accessibility for Deaf People. Third, Forms of legal remedies What can be taken by the deaf or deaf people when providing public information does not pay attention to their rights is to make an objection, send an open letter and submit a Judicial Review.Keywords: Broadcasting - Public Services - Information and Communication - Deaf Disabilities